Peran Tenaga Kesehatan Dalam Menurunkan Prevalensi Anemia Pada Remaja, dan Faktor Yang Mempengaruhi Terjadinya Anemia - Seftyani Lubis, Ade Irma; Maharani Hasibuan, Aisa; Riandini , Annisa; Ayenti, Erika; Ramadhani Saragih, Fahira; Ariansyah Sitorus, Fauji; Nisrina, Nisrina (Universitas Muhammadiyah Sukabumi, 2023)
Anemia is a disease characterized by lower-than-normal hemoglobin (Hb) levels in the blood. Hemoglobin is a protein in red blood cells that functions to transport oxygen from the lungs to the rest of the body. Based on the research findings, it is known that the role of Posyandu adolescents is to provide health services by health workers. The services provided are in the form of facilitators who will conduct health checks and refer adolescent girls diagnosed with anemia to the Puskesmas for hemoglobin testing. Since adolescent girls are at risk of anemia during menstruation, Posyandu Remaja needs to motivate them to take blood product tablets and undergo regular health checks every month. This study uses a literature review methodology that focuses on themes or variables obtained from previous research, namely written research (Wahyudi, 2022). Data regarding the role of health workers in reducing the prevalence of anemia in adolescents and factors influencing the occurrence of anemia were identified from research articles and literature reviews. Similar to Bangladesh and India, the prevalence of anemia in India is very high at 45.9%. One of the main factors causing anemia in adolescent girls is improper nutritional habits.